2014
DOI: 10.1152/ajpregu.00329.2013
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologically induced hypothermia via TRPV1 channel agonism provides neuroprotection following ischemic stroke when initiated 90 min after reperfusion

Abstract: Cao Z, Balasubramanian A, Marrelli SP. Pharmacologically induced hypothermia via TRPV1 channel agonism provides neuroprotection following ischemic stroke when initiated 90 minutes after reperfusion. Am J Physiol Regul Integr Comp Physiol 306: R149-R156, 2014. First published December 4, 2013; doi:10.1152/ajpregu.00329.2013.-Traditional methods of therapeutic hypothermia show promise for neuroprotection against cerebral ischemia-reperfusion (I/R), however, with limitations. We examined effectiveness and specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 55 publications
6
61
0
Order By: Relevance
“…77 DHC has been shown to be a specific and effective neuroprotective agent in inducing systemic hypothermia of 33.0 ± 0.2 °C after 100 min in a rodent stroke model. 78 Application of DHC (1.25 mg/kg) did not lead to similar reported cardiovascular depressive effects as capsaicin, with only a slight transient hypotension. 78 In rats given DHC via continuous IV infusion (at 1.0 mg/kg/hr for 5 total hours), there was reportedly increased susceptibility to hypotension and bradycardia in a cardiac arrest model.…”
Section: Unknownmentioning
confidence: 74%
See 1 more Smart Citation
“…77 DHC has been shown to be a specific and effective neuroprotective agent in inducing systemic hypothermia of 33.0 ± 0.2 °C after 100 min in a rodent stroke model. 78 Application of DHC (1.25 mg/kg) did not lead to similar reported cardiovascular depressive effects as capsaicin, with only a slight transient hypotension. 78 In rats given DHC via continuous IV infusion (at 1.0 mg/kg/hr for 5 total hours), there was reportedly increased susceptibility to hypotension and bradycardia in a cardiac arrest model.…”
Section: Unknownmentioning
confidence: 74%
“…78 Application of DHC (1.25 mg/kg) did not lead to similar reported cardiovascular depressive effects as capsaicin, with only a slight transient hypotension. 78 In rats given DHC via continuous IV infusion (at 1.0 mg/kg/hr for 5 total hours), there was reportedly increased susceptibility to hypotension and bradycardia in a cardiac arrest model. 72 This discrepancy could be explained by the latter study using much higher doses of DHC due to utilization of a continuous infusion method.…”
Section: Unknownmentioning
confidence: 74%
“…TRPV1 plays a thermoregulatory role and expresses mainly on a subset of sensory neurons in the peripheral and central nervous system, and TRPV1 activation might induce hypothermia (Gavva 2008) and ameliorate the injuries induced by ischemic insult (Khatibi et al 2011;Muzzi et al 2012;Cao et al 2014). Interestingly, our preliminary in vivo experiment observed that the reduction in the infarct area resulting from B-CA treatment was nearly reversed when the hypothermic effect was effectively inhibited by TRPV1 antagonist AMG517 (data not shown).…”
Section: Discussionmentioning
confidence: 88%
“…Several candidates targeting distinct signaling pathways have been tested for PIH including a neurotensin receptor agonist HPI201/ABS201 in stroke and TBI models [3, 4], a cannabinoid receptor agonist WIN55, 212-2 in a ventricular defibrillation CA model [5], the A1 adenosine receptor agonist 8-SPT in an asphyxial-CA model [6], the muscarinic cholinergic partial agonist U-80816E in the gerbil brief bilateral carotid occlusion ischemia model [7], a dopaminergic agonist Talipexole in stroke model [8], a serotonergic agonist S14671 in a stroke model [9] and the transient receptor potential cation channel vanilloid type 1 (TRPV1) agonist dihydrocapsaicin (DHC) in a stroke model [10]. …”
Section: Introductionmentioning
confidence: 99%
“…DHC, a capsaicin analog, is roughly 65% more effective than capsaicin in producing hypothermia [12], and is consequently a promising candidate for PIH. The capability of DHC to lower body temperature has been validated in healthy mice, rats, cows and monkeys [13, 14] and in stroke mice [10]. However, DHC has displayed cardiovascular effects [15], and whether CA victims could tolerate DHC has not been determined.…”
Section: Introductionmentioning
confidence: 99%